The Comparison of The Clinical Symptoms of Thypoid Fever in Adult Patients (Tubex vs Widal) in Banda Aceh, Aceh Province, Indonesia - Kurnia Fitri Jamil (Pusat Kedokteran Tropis, 2017)
Introduction: Salmonella typhi bacteria infects humans through food or water contaminated by feces or urine of the patients or asymptomatic career of typhoid fever. Currently the Tubex and Widal test are the standard test to establish a definitive diagnosis for typhoid fever in Aceh. Unfortunatelly little known the differences of the sensitivity and specificity of those two diagnostic tests in the relation to clinical symptoms in adult patients with typhoid fever in dr. Zainoel Abidin General Hospital (RSU.DZA) Banda Aceh. Objectives: To determine the differences in sensitivity and specificity between Tubex and Widal test in adult patients with typhoid fever and its relation to clinical symptoms in RSU.DZA. Methods: We condacted an descriptive analytic with a cross-sectional design. The subjects were 75 patients aged over 18 years. Data collected from the medical records (MR) since January to December 2013. Inclusion creteria were fever (>380C) between 5-21 days, or suspected typhoid fever, and diagnosed when admitted to hospital. All the patients were test with both diagnostic tools (Tubex and Widal).Results: Overall, from 75 sampels were tested. Most of the samples ages between 19-28 years old (45%) with male 69%. The sensitivity and specificity of the Tubex test was 84.21 % and 69.64 % respectively. 48.48 % positive predictive value (PPV) and negative predictive value (NPV)were 92.86 %. Fever was found in the whole subject of the research and became the main symptom of the patients when admitted to hospital, followed by headache, abdominal pain, nausea, vomiting and chills.Conclution: No differences of the Tubex and Widal test related to clinical symptoms and fever (>380C) was dominant funded. Keywords: Salmonella typhi, comparison, Tubex test, Widal test, RSU.DZA, Banda Aceh. INTISASRIPendahuluan: Penyakit infeksi Salmonella thyposa dapat ditularkan dari makanan dan air yang terkontaminasi dari faeses dan urine pasien yang terinfeksi Thypoid namun tidak menunjukkan gejala klinis. Saat ini penentuan diagnosis pada pasien thypoid menggunakan uji widal dan Tubex. Perbedaan nilai sensitifitas dan spesifisitas dari alat uji yang digunakan di Rumah Sakit Umum Dr. Zainoel Abidin (RSU. DZA) dalam menentukan diagnosis thypoid yang dihubungkan dengan gejala klinis pada pasien dewasa penting untuk dilakukan. Tujuan: Tujuan penelitian membandingkan nilai sensitifitas dan spesifisitas antara dua alat uji demam thypoid (Tubex vs Widal) yang dihubungkan dengan gejala klinis di RSU. DZA. Banda Aceh. Metode: Penelitian ini menggunakan metode deskriptif analitik dengan desain cross-sectional. Total sebanyak 75 pasien terlibat sebagai responden penelitian berdasarkan data medical record (MR) dari 01 januari-31 desember 2013. Pemilihan sampel berdasarkan usia lebih 18 tahun, adanya riwayat demam 5-21 hari, dan terdiagnosa suspek demam thypoid. Hasil: Nilai sensitivity dan spesifisitas dari alat uji Tubex= 84.21% dan 69.64%, dengan nilai positive predictive value 48.48% dan nilai negative predictive value= 92.86%. Simpulan: Tidak ada perbedaan pada nilai sensitivitas dan spesifisitas dari kedua alat uji (Tubex vs Widal test) berdasarkan gejala klinis. Demam, nyeri kepala dan mual muntah merupakan gejala klinisa terbesar ditemukan. Kata kunci: Salmonella thyposa, perbandingan, tubex test, widal test, RSU.DZA, Banda Aceh.